(Not) Thinking about the Future: Inattention and Maternal Labor Supply - Ana Costa-Ramón; Ursina Schaede; Michaela Slotwinski; Anne Ardila Brenøe (CESifo GmbH, 2024)
The “child penalty” significantly reduces women's lifetime earnings and pension savings, but it remains unclear whether these gaps are the deliberate result of forward-looking decisions. This paper provides novel evidence on the role of information constraints in mothers' labor supply decisions. We first document descriptively that mothers are largely inattentive to the long-term financial consequences of reduced hours. In a large-scale field experiment that combines rich survey and administrative data, we then provide mothers with objective, individualized information about the long-run costs of reduced labor supply. The treatment increases demand for financial information and future labor supply plans, in particular among women who underestimate the long-term costs. Leveraging linked employer administrative data one year post-intervention, we observe that mothers who underestimate the long-term costs increase their labor supply by 6 percent over the mean.
Keywords: J16; J22; 330